Translating awareness into action : what limits Finland’s domestic resource mobilization project for tax reform in Vietnam? - Aartola, Riikka (2021)
In the field of development finance and policy, there has been growing interest in the concept of domestic resource mobilization (DRM), a process whereby developing countries generate and spend their own funding to provide for their citizens and governments. DRM is mainly done by means of taxation, which is thought to improve public services, support state-building, reduce inequalities, and help realize Sustainable Development Goals. Yet despite increasing policy attention to DRM’s positive developmental impacts, there is noticeable inadequacy in academic research related to studying the relationship between taxation, governance and social reforms. In particular, research lags behind in meeting the necessity to study the role of civil society organizations in the DRM process. The present thesis aims to fill in this gap in information and literature by offering an empirical analysis of the case of the recent DRM project of both the Ministry for Foreign Affairs of Finland and the international development organization Oxfam for their partner country Vietnam. While the Finland-Oxfam project has some important gains, it has critical shortcomings specifically on translating improved societal awareness about tax-development nexus into effective implementation in the context of Vietnam. This study thus seeks to answer the main question: What are the factors that limit Finland’s DRM project in Vietnam? The research data analyzed come from official project documents and semi-structed interviews with five key informants. These empirical data are discussed with theoretical assumptions on taxation and DRM to examine the relationship between three concepts, or development principles, namely: ownership, citizen engagement, and fiscal contracts. The conclusions point to three interlinked factors that have constrained Finland-Oxfam’s DRM project: missing ownership principle in development effectiveness; limited political and civic space in Vietnam; and limitations of the fiscal contract proposition in the Vietnamese context. The thesis also hopes to contribute to discussions on the role of civil society in development cooperation, especially to provide information and insights into how donors can support non-government organizations in the DRM strategy. It does so by uncovering the conditions that limit civil society’s participation in some aspects of policy reforms and the development process.